Clinical, Neuroimaging, and Genetic Features of the Patients with L-2-Hydroxyglutaric Aciduria - Ebru Canda; Melis Köse; Havva Yazıcı; Esra Er; Cenk Eraslan; Ferda Özkınay; Mahmut Çoker; Sema Kalkan Uçar; Sara Habif; Emin Karaca; Hüseyin Onay (Galenos Yayinevi, 2018)
Aim:L-2-hydroxyglutaric aciduria (L2HGA) is a rare autosomal recessive encephalopathy caused by mutations in the L-2-hydroxyglutarate dehydrogenase gene.Materials and Methods:Here we discuss the clinical and molecular characteristics in patients with L2HGA.Results:There were eight patients with L2HGA. Their median age was 16 (9.5-37) years. Five of them were female and three of them were male. The main symptoms of the patients were psychomotor retardation (8/8), cerebellar ataxia (5/8), extrapyramidal symptoms (7/8) and seizures (4/8). All patients had behavioral problems. Elevated urinary L-2-hydroxy (L-2-OH) glutaric acid was detected and the median level of urine L-2-OH glutaric acid at diagnosis was 146 (60-1460 nmol/mol creat). Characteristic magnetic resonance imaging findings including subcortical cerebral white matter abnormalities with T2 hyperintensities of the dentate nucleus, globus pallidus and putamen were detected. Two patients had homozygous R335X, two patients had homozygous R282Q, two patients had homozygous R302L and one patient had compound heterozygous P302L/A64T mutation in L-2-hydroxyglutarate dehydrogenase (L2HGDH) gene.Conclusion:Because of the slow progression of the disease, the diagnosis of the patients is usually belated. L2HGA must be considered in the differential diagnosis based on clinical findings and specific findings in cranial magnetic resonance imaging. In our study, one of our patients has a novel mutation.